ANALISIS PERMINTAAN DAN PENAWARAN BERAS DI PROPINSI JAMBI - Edison, .; nurfathiyah, pera (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2012)
The rice production growth that was gotten by Jambi Province with production growth rate of 0,54% can not fully contribute society need that was continuously increasing. Therefore, it can cause unbalance between supply and demand. The objective of research is to know the picture of rice supply and demand and influenced variables on rice supply and demand in Jambi. The simultan model was used to predict factors that influenced rice supply and demand. The research was conducted in Jambi Province on September to December 2009. The primary data needed in this research was time series data from 1996 – 2008. The research result showed that simultaneously rice price factor, the number population and income per capita was significant on demand. And also factor of average rice price, Bangkok rice price, import rice price, hybrid seed, acreage, season, and time trend were influencing significantly on supply. From elasticity value was fortunately all variables that was influencing rice demand and supply in Jambi Province was inelastic. Kata Kunci : rice demand and supply, rice price, elasticit